Inflammatory and redox reactions in colorectal carcinogenesis. (27th February 2015) - Guina, Tina; Biasi, Fiorella; Calfapietra, Simone; Nano, Mario; Poli, Giuseppe
Abstract : It has been established that there is a relationship between chronic inflammation and cancer development. The constant colonic inflammation typical of inflammatory bowel diseases is now considered a risk factor for colorectal carcinoma (CRC) development. The inflammatory network of signaling molecules is also required during the late phases of carcinogenesis, to enable cancer cells to survive and to metastasize. Oxidative reactions are an integral part of the inflammatory response, and are generally associated with CRC development. However, when the malignant phenotype is acquired, increased oxidative status induces antioxidant defenses in cancer cells, favoring their aggressiveness. This contradictory behavior of cancer cells toward redox status is of great significance for potential anticancer therapies. This paper summarizes the essential background information relating to the molecules involved in regulating oxidative stress and inflammation during carcinogenesis. Understanding more of their function in CRC stages might provide the foundation for future developments in CRC treatment.